2015
DOI: 10.3389/fphys.2015.00234
|View full text |Cite
|
Sign up to set email alerts
|

Does the sympathetic nervous system contribute to the pathophysiology of metabolic syndrome?

Abstract: The metabolic syndrome (MS), formally known as syndrome X, is a clustering of several risk factors such as obesity, hypertension, insulin resistance, and dislypidemia which could lead to the development of diabetes and cardiovascular diseases (CVD). The frequent changes in the definition and diagnostic criteria of MS are indications of the controversy and the challenges surrounding the understanding of this syndrome among researchers. Obesity and insulin resistance are leading risk factors of MS. Moreover, obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 136 publications
(205 reference statements)
4
38
0
1
Order By: Relevance
“…Furthermore, the oxidative stress has been shown to be a major factor contributing to cardiac sympathovagal imbalance. Previous studies showed that oxidative stress leads to sympathetic hyperactivation in several pathological conditions including heart failure, aging, and obesity . In preclinical studies, sympathetic hyperactivation and a decreased LF/HF ratio were observed in HFD rats, together with increased oxidative stress markers such as malondialdehyde, superoxide anion, and F2‐isoprostanes .…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, the oxidative stress has been shown to be a major factor contributing to cardiac sympathovagal imbalance. Previous studies showed that oxidative stress leads to sympathetic hyperactivation in several pathological conditions including heart failure, aging, and obesity . In preclinical studies, sympathetic hyperactivation and a decreased LF/HF ratio were observed in HFD rats, together with increased oxidative stress markers such as malondialdehyde, superoxide anion, and F2‐isoprostanes .…”
Section: Discussionmentioning
confidence: 94%
“…Hypertension and diabetic Insulin. resistance was found to be associated with sympathetic overactivity, as observed in many patients 16 . Zorba et al 17 evaluated the impact of the autonomic nervous system on [24-hour] heart rate changeability in PE and reported that sympathetic activity was intensi ed in men with PE, especially the lifelong type.The overactivity in the sympathetic nervous system may produce initial pressure elevation in the male prostatic urethra and subsequent PE.…”
Section: Discussionmentioning
confidence: 73%
“…AIPE is a seven-question questionnaire that supports various items of sexual activity, including, libido (Q1), erection (Q2), intravaginal ejaculatory latency time (ELT) (Q3), control ejaculation (Q4), couple satisfaction (Q5-6) and the psychological in uence of PE (Q7) 10 . Results were classi ed as severe [7][8][9][10][11][12][13], moderate [14][15][16][17][18][19], mild-moderate [20-25] and mild [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…[12] Insulin resistance and subsequent hyperinsulinemia have been reported to activate the sympathetic nervous and the renin angiotensin systems resulting in endothelial dysfunction. [34,35] With reference to Laplace's law, high BP and obesity could trigger cardiac remodeling through hemodynamic and these humoral mechanisms and the thickening of cardiac wall may occur through collagen deposits. [36] Mehta et al in the Dallas Heart Study found LVH to be an independent risk factor for subclinical atherosclerosis diagnosed by cardiac MRI, coronary artery calcium, and C-reactive protein measurements.…”
Section: Discussionmentioning
confidence: 99%